ANALYSIS OF EMPLOYEE PERFORMANCE ASSESSMENT SYSTEM IN MANUFACTURING COMPANIES - Yusnita Effendy, Mutya (Proceeding International Seminar of Islamic Studies, 2022)
Employees are a very important factor in an organization to achieve organizational goals. Satisfactory performance from employees does not happen instantly but requires continuous evaluation. The results of this study indicate that performance appraisal has apositive and significant effect on employee performance. The purpose of this descriptive research is to make a systematic, factual and accurate assessment of the facts and nature of the employee performance appraisal system in a manufacturing company. This research is used to find out how the management information on the performance appraisal of manufacturing company employees. This shows that employees who are given a performance appraisal by their superiors make the employee's performance higher